Systemic BCG-Osis as a Rare Side Effect of Intravesical BCG Treatment for Superficial Bladder Cancer - S. Lukacs; B. Tschobotko; N. A. Szabo; Andrew Symes (Case Reports in Urology)
Intravesical Bacilli Calmette-Guérin (BCG) immunotherapy is a commonly used treatment for superficial bladder cancer. Although the treatment is well tolerated in 95% of cases, life-threatening side effects including BCG sepsis can occur. This report describes the case of an 82-year-old man with a background of lung disease. He developed septic shock and type two respiratory failure after receiving the sixth installation of intravesical BCG (TICE strain) immunotherapy for recurrent bladder Transitional Cell Carcinoma in situ. Despite the early initiation of broad spectrum antibiotics (tazocin and gentamicin), he remained pyrexial. There was a rapid deterioration, and on the second day of his admission, he developed type two respiratory failure secondary to Acute Respiratory Distress Syndrome (ARDS) prompting transfer to Intensive Care for Bilevel Positive Airway Pressure (BiPAP) Ventilation. The blood cultures taken before the induction of antibiotics results were negative. Increasing clinical suspicion of systemic BCG-osis prompted the initiation of antituberculosis therapy (ethambutol, isoniazid rifampicin) and steroids. Following six days of BiPAP and anti-tuberculosis therapy in ITU, his condition started to improve. Following a prolonged hospital stay he was discharged on long term ethambutol therapy. BCG-osis is a well-known though rare side effect of intravesical BCG therapy. We would like to highlight the importance of having a low threshold for starting anti-TB treatment.